Problem-oriented policing successful case studies - Scott, Michael S.; Clarke, R. V. G. (Crime science series, 2020)
"Problem-Orientated Policing: Successful Case Studies is the first systematic and rigorous collection of effective problem-oriented policing projects. It includes more than twenty case studies from among the thousands of projects submitted for the Herman Goldstein Award for Excellence in Problem-Oriented Policing. The volume describes in detail the case studies and explains the wider significance of each for effective, efficient, and equitable policing. This book explores a wide range of problems that fall under five general categories: gang violence; violence against women; vulnerable people; disorderly places; and theft, robbery and burglary. The case studies tell stories of how police, in collaboration with others, successfully tackled real-world policing problems fairly and effectively. The authors have also drawn out of the case studies the cross-cutting themes and issues they illustrate. The authors prove that the concept can work, bring to life the context in which police and communities addressed these vexing problems, and, ideally, will inspire future problem-oriented police work that builds upon these reported successes. Written in a clear and direct style, this book will appeal to students and scholars of policing, criminology, and social studies; police practitioners and crime analysts; and all those who are interested in learning more about the reality of police problem-solving"